Analisis Kadar Merkuri (Hg) dan Timbal (Pb) pada Air Sungai Batanghari di Daerah Hulu Kabupaten Dharmasraya Sumatera Barat - Ariani, Kori (journal of residu, 2019)
The river is one of the old used by man for a variety of activities in life, with the decline in the quality of human needs and river due to the presence of one of the various waste pollution accidents are heavy metals. This research aims to analyze the content of Pb, Hg and water quality standards based on raw fachir PP No 82 of 2001. This research was carried out in Januari, 2019.The sample using methods purposive sampling by observing four stations. Parameters observed fisika-kimia waters, is the parameter hg and pb on heavy metal concentration and water using atomic there water absorption spectrophotometry ( AAS). The level of heavy metals are on board in the highest station of a 0,447 mg /L based by Government Regulation no. 82 of 2001 and the quality of being inducted into a second, based on environmnetal quality standars and still classified as hight, the water out exceeding quality standards